PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH SELF-EFFICACY DAN KOMPETENSI TERHADAP KINERJA KARYAWAN INDUSTRI KREATIF DI JABODETABEK - Iwan Kresna Setiadi; Siti Hidayati; Guntur Syahputra Saragih; Muhaswad Dwiyanto (Gapenas Publisher, 2026)
This study aims to analyze the influence of self-efficacy and competence on employee performance, with job satisfaction as a mediating variable, in the creative industry in the Greater Jakarta area. The study employs an explanatory quantitative approach. The sample consisted of 385 employees in the creative industry in the Greater Jakarta area, selected using purposive sampling based on the study’s criteria. Data were collected via a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The analysis included an evaluation of the measurement model and the structural model, as well as testing of direct and indirect effects through bootstrapping procedures. The results indicate that self-efficacy and competence have a positive effect on job satisfaction. Job satisfaction also has a positive effect on employee performance. Conversely, self-efficacy and competence do not have a significant direct effect on performance. Job satisfaction was found to mediate the effects of self-efficacy and competence on performance through an “indirect-only” mediation pattern. The indirect effect of competence is greater than that of self-efficacy. The novelty of this study lies in identifying job satisfaction as an affective mechanism that transforms personal beliefs and actual capacity into performance within the context of the creative industry in the Greater Jakarta area. Implications: Organizations need to integrate competency development, self-efficacy enhancement, job design, rewards, organizational support, and increased job satisfaction to maintain creativity, adaptability, consistent quality, and sustainable employee performance in a dynamic, competitive, collaborative, and project-based work environment